Modular Integrated Probabilistic Model of Software Reliability Estimation - Tsarev, Roman Yu.; Chernigovskiy, Alexey S.; Shtarik, Elena N.; Shtarik, Andrey V.; Durmus, Mustafa S.; Ustoglu, Ilker (SLOVENSKO DRUSTVO INFORMATIKA, 2016)
A modular integrated probabilistic model of software reliability estimation and an algorithm of its application for estimation of software reliability with different architecture such as multilevel, multiversion, distributed and object-oriented ones are presented in the article. The modification of this model is given there for the object-oriented multiversion software with the distributed architecture. The procedure of its estimation is perfected to improve the quality of the reliability prediction. The description of the developed program system based on the modular integrated probabilistic model of reliability estimation of the object-oriented multiversion software with the distributed architecture is presented in the article. The analysis of relation of software reliability parameters to the component count, conditional and unconditional probability of the failure appearance in components and temporary components characteristics is done there as well.
Keywords: software reliability; reliability estimation; mean time to failure; mean time to repair; availability; multiversion software; Computer Science